Tertiary Palliative Care Model in South Africa: A case of the Gauteng/Wits Centre for Palliative Care - Ratshikana, Mpho; Mandikiana, Lawrence; Pilime, Sukoluhle; Makume, Phillip; Sobekwa, Mfanelo; Lorenz, Karl; Breuk, Cara de; Tsitsi, Merika (Archives of Clinical and Biomedical Research, 2024)
Background: Palliative care is an essential part of universal health coverage. Access to palliative care remains limited. The Wits Centre for Palliative Care (WPC) at the Chris Hani Baragwanath Academic Hospital (CHBAH) in Soweto, South Africa, is one of the pioneer institutions addressing this gap. By adopting a multifaceted model of care, WPC aims to provide equitable access to comprehensive palliative care services. Aim: This review aims to evaluate the WPC model of care and assess the extent to which the model provides access to palliative care services, enhances patient and family support, and promotes sustainability and replicability. Program Strategies: The WPC boasts three models; in-patient model supporting patients admitted in the CHBAH wards, out-patient model supporting discharged and walk-in patients; as well as the home care model for patients with low functional status. These models are complemented through five strategies: Collaboration, Clinical Services, Training, Research, Advocacy and Awareness. Outcomes: Major achievements include provision of comprehensive patient-centred care, producing peer-reviewed publications and training health professionals. Lessons Learned and Replicability Potential: Sustaining the WPC model required integration within the health care system. All models reduce pressure on hospital services and empower families and patients, improving patient`s quality of life. Training and research are key to support service delivery. This model can be replicated by any country/ region with adaptation of strategies to local needs/conditions. Conclusion: WPC's multifaceted model of care serves as a valuable framework for advancing palliative care provision, offering insights into operational strategies, successes, challenges, and replicability potential.